Methadone maintenance therapy in Selangor state, Malaysia: factors associated with program effectiveness and client satisfaction / Nirmalah Subramaniam - Nirmalah, Subramaniam (2018)
Successful patient outcome in methadone maintenance program is a result of long term treatment and rehabilitation. Therefore evaluation of treatment should consider successful outcome as a status of patients after months and years of therapy. Patients‟ satisfaction with methadone maintenance treatment (MMT) is a key measure of treatment quality. The aim of this study was to explore the quality of life of clients who was addicted to heroin and their responses at baseline and after joining the Methadone Maintenance Therapy and how quality of life can be successfully integrated in the treatment as well as to identify factors that are associated with quality of life of methadone clients. Attention is also given to find out how much of these clients satisfied with the program modality and also to explore the factors that predict the employment outcome after joining the program. This study includes retrospective record review and cross-sectional component among all active clients in methadone treatment between years 2007 and 2012. The study was conducted at government hospitals and primary health care centres in the state of Selangor. Total of 12 Methadone clinics participated in this study. Face-to-face interviews guided by structured questionnaires were conducted by the researcher using a set of questionnaires namely, WHO Quality of Life-BREF (WHOQOL-BREF), Opiate Treatment Index (Health et al.) and Patient‟s Satisfaction Questionnaire III (PSQ). After applying the inclusion and exclusion criteria total of 661 clients were included in this study. Quality of life of methadone clients showed a significant improvement in all domains with p iv values < 0.001 at baseline and after joining the program. In a multivariate analysis, being employed, hepatitis B virus (HBV) negative, hepatitis C virus (HCV) negative, Human immunodeficiency virus (HIV) negative, married, age between 30-50 years old, race, male, dose and years of drug use were the significant predictors of the magnitude of quality of life of methadone clients. . More than 90% of the clients were satisfied with service provided. Years of drug use (11 – 20years), HCV negative status and HBV negative status were the predictors for the level of satisfaction. Being male (AOR 8.60, 95% CI 2.71, 27.30), unemployed before starting treatment (AOR 8.18, 95% CI 4.80, 13.94) and HIV negative (AOR 3.02, 95% CI 1.43, 6.34) were found to be associated with current employment status. The application of methadone maintenance treatment program has been considered as an effective in enhancing the outcomes of employment, reducing the criminal activities, decrease the use of the drug and risky behaviours related to blood-borne diseases while leading to an improved social behaviour and life. Clients on methadone program have a significant quality of life in all domains after joining the program. Treatment satisfactions survey revealed that most clients have overall satisfaction with health care workers and service. Employment status is commonly upheld as a very important outcome. Total of 84% of clients‟ are employed while in treatment. The methadone maintenance treatment program has great prospects in the treatment of opioid addiction and it is important to ensure the improvement is sustained.